PROFIL LAJU ENDAP DARAH (LED) DAN HEMATOKRIT PADA PENDERITA TUBERKULOSIS DI WILAYAH PUSKESMAS PADANG SERAI KOTA BENGKULU - Mardiyansyah Bahar (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Mycobacterium tuberculosis infection causes tuberculosis, which is a long-term disease. Tuberculosis can attack the lungs and then attack other organs in a person's body. The purpose of this study is to find out the description of blood sediment and hematocrit values in tuberculosis patients treated at the Padang Serai Health Center, Bengkulu City. Sampling was done using the Purposive Sampling technique. This research was conducted in the clinical chemistry laboratory of the Academy of Health Analysts Harapan Bangsa Bengkulu with a sample of 17 tuberculosis patients. The results of the examination in tuberculosis patients showed that 3 respondents with a percentage (17.6%) had a normal Blood Sedimentation Rate and 14 respondents with a percentage (82.4%) experienced an increase in Blood Sedimentation Rate. For the results of the Hematocrit examination, 8 Tuberculosis patients with a percentage (47%) had normal Hematocrit values and 9 Tuberculosis patients with a percentage (52.9%) had a decreased hematocrit niai. Keywords: Tuberculosis, Blood Precipitation Rate, Hematocrit